Epileptic Seizure, Postictal Hemiparesis, and Hyperleukocytosis. (13th December 2016) - Olivieri, Martin; Kurnik, Karin; Heinen, Florian; Schmid, Irene; Hoffmann, Florian; Reiter, Karl; Gerstl, Lucia
Introduction: Acute ischemic stroke (AIS) is a rare event in infancy. Besides vasculopathy, thrombophilia, or cardiac disorders, cancer and chemotherapy are known predisposing factors for AIS. Leukemia can be associated with different abnormal coagulation parameters, but severe bleeding or thrombosis occurs rarely.Clinical Course: We report the case of a 2-year-old boy who was presented to our emergency ward after a prolonged seizure with right sided postictal hemiparesis. Cranial computed tomography scan revealed a large infarction and edema due to thrombosis of the left carotid artery, the middle cerebral artery, and the anterior cerebral artery. Laboratory workup showed 196 g/L leukocytes with 75% myeloid blast cells. Immediate exchange transfusion, hydration, and chemotherapy with cytarabine were started. During the hospital course intracranial pressure increased and the patient developed a unilateral dilated pupil unresponsive to light. Cranial computed tomography scan revealed a new infarction in the right middle cerebral artery territory. Refractory increased intracranial pressure and brain stem herniation developed, and the child died 3 days after admission to hospital.Conclusion: Seizures with postictal hemiparesis due to cerebral infarction can be a rare manifestation of acute myeloid leukemia. Leukocytosis and cancer-induced coagulopathy are main reasons for thrombosis and/or hemorrhage. High leukocyte counts need immediate interventions with hydration, careful chemotherapy, and perhaps exchange transfusion or leukapharesis. In the presence of thrombosis, anticoagulation must be discussed despite the risk of bleeding due to hyperfibrinolysis and low platelet counts. Mortality may be reduced by awareness of this rare presentation of leukemia and prompt institution of leucoreductive treatment.